Comparative Analysis of Singular Value Decomposition and Eigenvalue Decomposition Methods for Solving Large Scale Linear Systems (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study compares the effectiveness of Singular Value Decomposition (SVD) and Eigenvalue Decomposition in solving large-scale linear systems, focusing on computational efficiency, numerical stability, and versatility across different problem domains. At its core, matrix decomposition is a crucial tool in numerical linear algebra, allowing us to break down complex systems into more manageable forms.The study delves into both the theoretical underpinnings and practical performance of these methods, highlighting their respective strengths and weaknesses. SVD stands out for its ability to handle ill-conditioned matrices and is widely used in dimensionality reduction and data analysis, whereas Eigenvalue Decomposition is commonly applied to structured problems and spectral analysis.To validate the performance claims, computational experiments were conducted using randomly generated matrices of sizes 100×100, 1000×1000, and 5000×5000. The results show that both methods perform efficiently for small matrices, but as matrix size increases, SVD demonstrates better computational performance on the tested system. Moreover, for large and ill-conditioned matrices, SVD exhibits superior numerical stability, making it a more reliable choice than Eigenvalue Decomposition.The study also explores applications in machine learning, optimization, artificial intelligence, recommender systems, and structural engineering to illustrate the practical relevance of these findings. Ultimately, the choice of method depends on the specific problem at hand, requiring a trade-off between computational efficiency, numerical stability, and scalability.